Hadith #683 - Sahih al-Bukhari - Muadh ibn Jabal (Sahih al-Bukhari)
I used to pray the `Isha prayer with the Prophet (ï·º) and then go to lead my people in the prayer.
Grade: Sahih

Hadith #5739 - Sahih al-Bukhari - Muadh ibn Jabal (Sahih al-Bukhari)
While I was riding behind the Prophet (ï·º) and between me and him and between me and him there was only the back of the saddle, he said, â0 Mu`adh!â I replied, âLabbaik, 0 Allahâs Messenger (ï·º), and Sa`daik!â he said, âDo you know what is Allahâs right upon his slave?â I said, âAllah and His Apostle know bestâ He said âAllahâs right upon his slaves is that they should worship Him alone and not worship anything else besides Him.â Then he proceeded for a while and then
Grade: Sahih

Hadith #6261 - Sahih al-Bukhari - Muadh ibn Jabal (Sahih al-Bukhari)
While I was riding behind the Prophet (ï·º) as a companion rider and there was nothing between me and him except the back of the saddle, he said, âO Mu`adh!â I replied, âLabbaik O Allahâs Messenger (ï·º)! And Sa`daik!â He proceeded for a while and then said, âO Mu`adh!â I said, âLabbaik and Sa`daik, O Allahâs Messenger (ï·º)!â He then proceeded for another while and said, âO Mu`adh bin Jabal!â I replied, âLabbaik, O Allahâs Messenger (ï·º), and Sa`daik!â He said, â
Grade: Sahih

Hadith #7092 - Sahih al-Bukhari - Muadh ibn Jabal (Sahih al-Bukhari)
The Prophet (ï·º) said, âO Mu`adh! Do you know what Allahâs Right upon His slaves is?â I said, âAllah and His Apostle know best.â The Prophet (ï·º) said, âTo worship Him (Allah) Alone and to join none in worship with Him (Allah). Do you know what their right upon Him is?â I replied, âAllah and His Apostle know best.â The Prophet (ï·º) said, âNot to punish them (if they do so).
Grade: Sahih